IMPROVING STUDENT LEARNING INDEPENDENCE TOWARDS PROJECT-BASED LEARNING MODEL: A CASE STUDY IN MAKING HERBARIUM NAME CARD PRODUCTS - Purnomo, Agung; Ekantini, Anita (Sanata Dharma University Yogyakarta, 2023)
The independence of student learning is one aspect to determine the success of student learning, but the fact is that there are still many students who need to be more independent in learning. This research will evaluate whether the project-based learning (PjBL) model can improve student learning independence (SLI). This study is a quantitative research using a quasi-experimental method. Pretest-postest group design was employed as the research design. The object was students from year seven class B and D LHI Islamic Junior High School in the first semester of the academic year 2022/2023, which were selected using the classroom random sampling technique. The findings indicate that this model applied to science learning with the herbarium project can increase SLI due to the requirement of being independent during completing an individual project. In addition, for future works, it could add new activities which also maximize collaboration among students in completing their projects in conjunction with independence.